2020
DOI: 10.1186/s13287-020-01844-y
|View full text |Cite
|
Sign up to set email alerts
|

Rat epidermal stem cells promote the angiogenesis of full-thickness wounds

Abstract: Background: Full-thickness wounds severely affect patients' life quality and become challenging problems for clinicians. Stem cells have great prospects in the treatment of wounds. Our previous study confirmed that autologous basal cell suspension could promote wound healing, and epidermal stem cells (ESCs) were detected in the basal cell suspension. Herein, this study aimed to explore the effect of ESCs on full-thickness wounds. Methods: Rat ESCs were isolated and expanded and then were transfected with lenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…A large number of researches have demonstrated that the growth of new blood vessels could form the granulation tissue and improve wound microcirculation. [53][54][55] In order to evaluate the efficacy of the hydrogel dressing in preventing infection, tumor necrosis factor-alpha (TNF-) and interleukin 6 (IL-6), which are known to play a key role in stimulating the inflammatory response, were selected as the indicators to assess the inflammation of wounds on the 7th day. The immunofluorescence staining and quantitative analysis results of TNF-and IL-6 are shown in Figure 7a,b, which reveal the higher expression of TNF-(P<0.05) and IL-6 (P<0.01) in the control group than that in the PNA-G/NIR group.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
“…A large number of researches have demonstrated that the growth of new blood vessels could form the granulation tissue and improve wound microcirculation. [53][54][55] In order to evaluate the efficacy of the hydrogel dressing in preventing infection, tumor necrosis factor-alpha (TNF-) and interleukin 6 (IL-6), which are known to play a key role in stimulating the inflammatory response, were selected as the indicators to assess the inflammation of wounds on the 7th day. The immunofluorescence staining and quantitative analysis results of TNF-and IL-6 are shown in Figure 7a,b, which reveal the higher expression of TNF-(P<0.05) and IL-6 (P<0.01) in the control group than that in the PNA-G/NIR group.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
“…To assess the condition of wound healing in mouse backs, the wound was photographed by a digital camera (Nikon, Tyoto) on days 0, 3, 7, and 14 ( Huang et al, 2020 ). The wound closure rate was quantified by ImageJ software (Bethesda, MD) and calculated as follows: t-t 0 /t 0 × 100% (t: the wound healing was assessed, t 0 : initial wounding).…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…Our previous study showed that EpSCs could proliferate and differentiate in the wound bed and observed that EpSCs form new blood vessels in the wound bed [ 23 ]. We hypothesized that the vascularization process inside the dermal substitutes implanted into the wound was similar to that in the site of damage.…”
Section: Introductionmentioning
confidence: 99%